دور الجمارك الجزائرية في تسهيل عمليات التصدير - بوترعة, محمد يزيد; معروفي, نبيلة; طبية, صابرينة (university of eloued, 2018)
تطرقنا في هذه الدراسة لموضوع دور الإدارة الجمركية في تسهيل عملية التصدير وذلك من خلال دراسة الإجراءات الجمركية متعلقة بالتصدير على المستوى النظري ثم محاولة إسقاط ذلك على واقع الاقتصاد الجزائري خلال الفترة (2010-2016) . ولتحقيق ذلك قمنا بدراسة ميدانية إلى شركة تريمكس بالتنسيق مفتشية أقسام الجمارك بالوادي حيث أشرفنا على عملية تصدير بمنطقة العبور الطالب العربي. وذلك من خلال الوكيل المعتمد لدى الجمارك تريمكس لصالح الشركة COPS SCHLU MBERER حاسي مسعود بطلب تصدير نهائي لعتاد مستورد في إطار الاستهلاك بدون تحويل وذلك بالإلمام بجميع الإجراءات المتعلقة بعملية التصدير, على مستوى إدارة الجمارك بالطالب العربي In this study, we discussed the role of the customs administration in facilitating the export process through studying the customs procedures related to export at the theoretical level and then trying to bring this down to the reality of the Algerian economy during the period2010-2016. In order to achieve this, we conducted a field study to TRIMEX in coordination with the customs departments of the Valley, where we supervised the export process in the Arab student transit area. Through the agent authorized by the Customs Tarimax for the company. COPS SCHLU MBERER HassiMassoud has applied for the final export of imported equipment in the framework of consumption without conversion, knowing all procedures related to the export process, at the level of the customs administration of the Arab student
مذكرة ماستر تجارة دولية
Keywords: إدارةالجمارك -التصدير - الإجراءاتالجمركية